The Effects of Audit Committee on Internal Audit Department: A Study on the Perceptions of Chief Audit Executives in the Context of Turkey - Batuhan F. MOLLAOĞULLARI (Yönetim ve Ekonomi, 2020)
Internal audit function significantly contributes to a higher transparency and accountability vision within a corporate governance framework, which is only possible through solid collaboration of the internal audit committee. A staunch connection between internal audit function and internal audit committee has direct influence on organizational effectiveness and efficiency. Accordingly, the efficiency and effectiveness of the aforesaid relationship between internal audit unit and audit committee plays a particularly critical role in organizational decision making processes. In addition, chief audit executive has a key role in developing more prolific relations between internal audit unit, corporate management and audit committee. To guarantee further efficiency of the business processes, chief audit executive should coordinate cross-functional relationships in a such a way to avoid any misunderstandings. This study problematizes the interaction between audit committee and internal audit unit through chief audit executives’ perceptions. The findings of the empirical study show that chief audit executive of companies with an internal audit committee where direct reporting is not the norm have less than perceptions of independence.